The Influence of Water and Solvent Uptake on Functional Properties of Shape-Memory Polymers - Ehsan Ghobadi; Axel Marquardt; Elias Mahmoudinezhad Zirdehi; Klaus Neuking; Fathollah Varnik; Gunther Eggeler; Holger Steeb (International Journal of Polymer Science)
In this contribution, diffusion of water, acetone, and ethanol into a polymer matrix has been studied experimentally and numerically by finite element approaches. Moreover, the present study reports an assessment of different thermomechanical conditions of the shape-memory (SM) performance, for example, stress- or strain-holding times in stress- or strain-controlled thermomechanical cycles and the effect of maximum strain. According to the results presented here, the uptake of acetone in Estane is much higher than ethanol and follows classical Fickian diffusion. Further, a series of thermomechanical measurements conducted on dry and physically (hydrolytically) aged polyether urethanes revealed that incorporation of water seems to have an appreciable impact on the shape recovery ratios which can be attributed to the additional physical crosslinks. However, no obvious difference in shape fixation of dry and physically (hydrolytically) aged samples could be recognized. Furthermore, by decreasing the strain-holding time, shape recovery improves significantly. Moreover, the shape fixity is found to be independent of holding time. The shape recovery ratio decreased dramatically with an increase in the stress-holding time.